STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PADA DAVONNA BEAUTY STORE - Kevin Ali Piaggio; Anita Zilvana (CV. Adiba Aisha Amira, 2025)
This research shows that increasing sales at the Davonna Beauty Store can be achieved through the implementation of planned and targeted marketing strategies. Several steps that can be taken include market analysis and customer segmentation to understand consumer needs and preferences. In addition, utilizing digital platforms, such as social media and influencer marketing, will help increase brand awareness and attract new customers. Attractive promotions, such as discounts, product bundling and loyalty programs, can strengthen relationships with existing customers and attract new consumers. Improving customer experience through optimal service and ease of shopping, both offline and online, is also a key factor in driving sales. With the right marketing strategy, Davonna Beauty Store can strengthen its competitive position and achieve significant sales growth.